Effect of boron toxicity on pollen tube cell wall architecture and the relationship of cell wall components of Castanea mollissima Blume - Zhang, Weiwei; Zhang, Qing; Xing, Yu; Cao, Qingqin; Qin, Ling; Fang, Kefeng (Frontiers in Plant Science, 2022)
Boron (B) is essential to plant development. However, excessive B is toxic to plant. This research was performed to evaluate the effects of B toxicity on cell wall architecture of Castanea mollissima Blume pollen tubes with emphasis on relationship among pectin, cellulose and callose. Results showed that 0.05 % B inhibited pollen germination and led to abnormal morphology of the pollen tubes. B toxicity also affected the distribution of cell wall components of the pollen tube. In control pollen tube, esterified and acid pectins distributed unevenly, with the former mainly at the tip, while the latter on the distal region. Cellulose distributed uniformly on the surface with less at the tip; callose reduced gradually from base to sub-tip of the pollen tubes and no callose at the tip of the tube was detected. B toxicity led to deposition of esterified and acid pectin, cellulose and callose at the tip of pollen tube. Results from scanning electron microscopy and transmission electron microscopy showed that B toxicity also altered pollen tube wall ultrastructure. The results from enzymatic treatment illustrated that there existed a close relationship among pectin, cellulose, and callose. B toxicity also altered the relationship. In a word, B toxicity altered deposition and relationship of pectins, cellulose and callose of pollen tube wall.